Integrating network pharmacology and experimental validation to explore the mechanism of action of BushenQiangxin Formula for the treatment of chronic heart failure - Jinhua Pang; Jiejun Hou; Jinyi Chen; Wenchu Zhao; Tiantian Tang; Taotao Li; Ding Liu; Jinkai Li; Xuan Wang (Pharmacological Research - Modern Chinese Medicine)
Objective: : To evaluate the mechanism of action of the BushenQiangxin (BSQX) formula in treating chronic heart failure (CHF) based on network pharmacology and experimental zoology. Methods: : The targets and components of BSQX in CHF were assessed based on network pharmacology and data from the Gene Expression Omnibus (GEO) database. The drug–disease interaction network diagram was constructed, and the possible pathways affected by BSQX in CHF were analyzed. Molecular docking between the key components of BSQX and the key targets of CHF was performed using the Discovery Studio software. Finally, a CHF rat model was established. The serum interleukin (IL)-6 level was evaluated using the enzyme-linked immunosorbent assay in each rat group. The structural changes in the left ventricular myocardial tissues were observed via hematoxylin & eosin staining, and the expression of cTnI, IL-17, and nuclear factor kappa B (NF-KB) proteins was measured via immunohistochemistry in the cardiac muscle tissue. Results: : Network pharmacology and data from the GSE84796 database were used to screen 25 core targets of BSQX for CHF. The major signaling pathways, including the IL-17 signaling pathway, tumor necrosis factor signaling pathway, AGE-RAGE signaling pathway, which are associated with diabetic complications, lipid, and atherosclerosis were identified via Gene Ontology and Kyoto Encyclopedia of Genes and Genomes enrichment analysis. The molecular docking results showed good binding between the core targets (IL6, MMP9, CCL2, and STAT1) and active compounds (such as quercetin, lignocerol, oleanolic acid, pentacosanoic acid, and isobetulinic acid). Hematoxylin & eosin staining in animal experiments showed that BSQX could reduce the degree of inflammatory infiltration and fibrosis of cardiomyocytes in CHF to a certain extent. The enzyme-linked immunosorbent assay and immunohistochemistry showed that BSQX could effectively reduce the levels of IL-17, IL-6, cTnI, and NF-KB in chronic rats. Conclusion: : In CHF treatment, the mechanism of BSQX can be related to the inhibition of IL-17, IL-6, cTnI, and NF-KB production, inflammatory cell infiltration, and the attenuation of myocardial injury based on network pharmacology and experimental animal studies. Moreover, its mechanism of action may function via the IL-17 signaling pathway.